2019
DOI: 10.3390/ijerph16193666
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Childhood Maltreatment and Risky Sexual Behaviors: A Meta-Analysis

Abstract: Childhood maltreatment is associated with risky sexual behaviors (RSBs). Previous systematic reviews and meta-analysis focused only on the relationship between childhood sexual abuse and RSBs, thus the association between childhood maltreatment and RSBs has yet to be systematically and quantitatively reviewed. We aimed to provide a systematic meta-analysis exploring the effect of childhood maltreatment and its subtypes on subsequent RSBs in adolescence and adulthood. PubMed, Google Scholar, EMBASE, Medline wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…The present study replicated these results, showing that men who had experienced more childhood emotional abuse reported greater sexual sensation seeking, which was subsequently associated with state impulsivity, state anxiety, and coercive CUR. Thus, it follows that men who experienced greater levels of childhood emotional abuse are not only at an increased risk of engaging in impulsive behaviors during risky sexual encounters (Abajobir et al, 2018; Wang et al, 2019), but also at greater risk for perpetrating sexual aggression in the form of coercive CUR. As such, intervention programs seeking to reduce coercive CUR perpetration should consider screening for and targeting individuals who experienced greater levels of childhood emotional abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The present study replicated these results, showing that men who had experienced more childhood emotional abuse reported greater sexual sensation seeking, which was subsequently associated with state impulsivity, state anxiety, and coercive CUR. Thus, it follows that men who experienced greater levels of childhood emotional abuse are not only at an increased risk of engaging in impulsive behaviors during risky sexual encounters (Abajobir et al, 2018; Wang et al, 2019), but also at greater risk for perpetrating sexual aggression in the form of coercive CUR. As such, intervention programs seeking to reduce coercive CUR perpetration should consider screening for and targeting individuals who experienced greater levels of childhood emotional abuse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, adolescents who experienced more harshness, as operationalized by exposure to violence, was less sexually restricted (Brumbach et al, 2009). Similarly, a meta-analysis has demonstrated that childhood maltreatment, an example of environmental harshness, was associated with earlier sexual debut and having multiple sexual partners in adolescence and adulthood (Wang et al, 2019). Ecological harshness has also been linked to faster life history strategies, such that younger women residing in neighborhoods with lower life expectancy gave birth at an earlier age (Wilson & Daly, 1997).…”
Section: Empirical Evidence For Harshness and Unpredictabilitymentioning
confidence: 99%
“…As well as mental disorders, children exposed to CM are at risk for impaired cognitive development, asthma, sleep disruptions, somatic complaints such as headache and nausea, and recurrent infectious diseases requiring hospitalization (21). CM is also consistently related to poorer long-term physical health and problematic health behaviors such as diabetes, chronic pain, chronic inflammatory states, obesity, physical inactivity, smoking, increased suicidal behavior, poor sexual health and risky sexual behaviors (3,(22)(23)(24)(25)(26)(27). Further, there is a well-documented risk for substance abuse and corresponding disorders in both children and adults exposed to CM (28) -conditions which incur significant costs for society (e.g., more than $193 billion per year in the US; (29)).…”
Section: Effects Of Child Maltreatment On Mental and Physical Healthmentioning
confidence: 99%